2021
DOI: 10.1186/s12887-021-02645-9
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric flat foot and foot dimension in Central Anatolia

Abstract: Background Information on the foot structures of Central Anatolian children is limited. Foot structures of children aged 6–10 years were shown to be different according to sex and increasing age. Objective This study aimed to compare the foot anthropometric values by age and sex and collect the foot anthropometric data to reveal the relationship between pes planus and pes cavus in the arches of children according to age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
(7 reference statements)
2
6
0
Order By: Relevance
“…Similar to the results of other studies [14,16,17], we also detected a decreasing trend in the prevalence of childhood flat feet with increasing age. Between younger (11.3%) and older (8.2%) schoolchildren, were found statistically significant differences in the prevalence of flat foot (the greater number is present in earlier grades).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the results of other studies [14,16,17], we also detected a decreasing trend in the prevalence of childhood flat feet with increasing age. Between younger (11.3%) and older (8.2%) schoolchildren, were found statistically significant differences in the prevalence of flat foot (the greater number is present in earlier grades).…”
Section: Discussionsupporting
confidence: 91%
“…The results showed significant differences in the prevalence of flat feet, depending on some socio-demographic variables (age and material status) and nutritional status. Alsancak et al [14] and Yin et al [15] showed that three variables had a significant relationship with the prevalence of flat foot: age, sex, and weight. Our study demonstrates that the prevalence of flat feet in schoolchildren is not influenced by gender, although the percentage distribution of flat feet was higher in (10.8%) than girls (8.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Alsancak et al [ 39 ] revealed that foot structures in Anatolian children aged 6 to 10 years differed depending on sex and age. Age, gender and body weight were associated with foot dimensions and pes planus diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The foot arch is developed with increasing age [ 25 ] which may explain the foot height development. However, a flat foot is a normal finding in early childhood periods [ 25 , 26 ]. In addition, there was no association between increased body mass and foot arch in children [ 27 ].…”
Section: Discussionmentioning
confidence: 99%